Characterization of solder/UBM interface and materials properties - Ong, Kai Yie. (2010)
Various attempts, such as varying the thickness and phosphorus content, have been made to slow down the consumption of UBM and formation of IMC. The current project chooses to focus on Ni-Sn-P UBM alloy. There is not much literature concerning Ni-Sn-P UBM alloy therefore more efforts have to be made to examine the interfacial reactions, the mechanical reliability and the effect of tin concentration on reliability of electroless Ni-Sn-P with the solder. Samples were reflowed for 1, 3 and 5 cycles for 60 seconds at 260 °C and tensile test is performed to test the mechanical reliability of the joint. 2 layers of IMC are formed on electroless Ni-Sn-P layer and they are Ni3Sn4 and a compound with the following composition, Ni 70.66at% Sn 1.54at% P 27.80at%. Cross section of solder joints for electroless Ni-Sn-P with high tin shows thick layer of Ni3Sn4 and layers with compositions comprising of Ni 61.28at%, Sn 20.42at%, P 18.30at% and Ni 72.93at% and Sn 13.29at%, P 13.78at% respectively. All electroless Ni-P samples showed ductile failure in all the solder. Both electroless Ni-Sn-P samples with low tin and high tin which had undergone 1 cycle of reflow experiences ductile failure in the solder joint whereas samples that had undergone 3 cycles and 5 cycles of reflow both experiences bulk and interfacial failure. Tensile strength for samples with 5 cycles of reflow have lower strength than those with 3 cycles of reflow.